Kecoa: Ancaman Tersembunyi Bagi Kesehatan Manusia - Rara Londok; Melky Pangemanan; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Cockroaches are common pests found in urban environments and can pose a serious threat to human health. This study aims to examine the health impacts caused by cockroaches, including allergies, asthma, and infectious diseases. Through a literature review and epidemiological data analysis, the research finds that cockroaches can cause allergies and exacerbate asthma symptoms through allergens present on their bodies and excrement. Additionally, cockroaches have the potential to act as vectors for infectious diseases such as salmonellosis and gastroenteritis by spreading pathogenic bacteria. The findings of this study indicate that cockroach infestations are a significant health issue and require special attention in pest control efforts and public education. Implementing integrated pest management strategies and improving environmental cleanliness are expected to reduce the health risks posed by cockroaches.